Teenagers' Perceptions of Modern Trends that Conflict with Religious Values in Yogyakarta - Intan Dwi Saputri; Fitriah M. Suud (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Teenagers, who should be the golden generation by increasing their knowledge and trying various things, have now become trapped in a superficial consumption of trends, sacrificing their potential for growth. This study aims to examine teenagers' perceptions of modern trends that contradict religious values in Yogyakarta. This research employs a qualitative approach using interviews and documentation techniques. The interview technique is used to gather accurate information from reliable informants, while documentation is employed to obtain data, knowledge, and accurate evidence. The findings indicated that today's teenagers are easily drawn into modern trends that contradict religious values. The main challenge faced by teenagers is the pressure to either follow trends or stay true to their beliefs, which can lead to disturbances in their mental or psychological health. However, this study also finds that some teenagers still firmly uphold and strengthen their faith, making them less susceptible to modern trends that conflict with Islamic religious values. Here, the role of Islam is significantly influential in shaping the character and morals of teenagers in this challenging era of globalization.